Pengaruh Kualitas Pelayanan TerhadapKepuasan Pelanggan Pada Bengkel Mobil IinJaya Pekanbaru - Syafrina, Nova; Pasaribu, Fran Mikail (Eko dan Bisnis: Riau Economic and Business Review, 2025)
This research was carried out to determine the effect of service quality on customer satisfaction at the Iin Jaya Pekanbaru car repair shop. The sample in this research was all 95 customers. Samples were taken from 95 people using the Slovin formula with an accidental sampling technique. Data analysis in this research uses descriptive and quantitative analysis methods. From the descriptive analysis, it was found that the respondents' response to the Service Quality variable statement was an average of 3.93 (Agree). Furthermore, the respondents' responses to the Customer Satisfaction variable statement were an average of 3.95 (Agree). The results of simple linear regression research in this study were Y = 28.645 + 0.470. By using the t test, the ttable value was obtained at 1.985 and the tcount value was 4.850, meaning tcount = 4.850 > ttable = 1.985, which means that service quality influences customer satisfaction at the Iin Jaya Pekanbaru car repair shop with a large influence of 20.2%